Pemodelan Fotovoltaik Berbasis Teknik Adaptive Neuro Fuzzy Inference System - Tribowo, Ihwallibi; Zakri, Azriyenni Azhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Photovoltaic system is designed to meet the need of electricity or as an alternative energy. Using of photovoltaic panel system to generate electrical power has uncertainty of output power value, since it is not constant and strongly influenced by weather condition. This research discusses photovoltaic model to predict efficient and accurate output. This modelling system will applies method of Adaptive Neuro Fuzzy Inference System (ANFIS) to generate power, voltage, current, and temperature prediction. This model is divided into two systems run by ANFIS, ANFIS system 1 and system 2. From simulation result, obtained error value of open circuit voltage from battery 0.000104 %. This value is output value of ANFIS system 1. Furthermore, simulation of ANFIS system 2 produces error value of AC voltage around 0,058482%, This value is the output of inverter.Keyword : ANFIS, battery, modeling, prediction, photovoltaic